ROLE OF LAPROSCOPY IN DETECTING PELVIC CAUSES OF FEMALE SUBFERTILITY IN OBSTETRICS AND GYNAECOLOGY UNIT PESHAWAR - Farhad, Umaiyma; Akbar, Saima; Sumayya; Amina, Noor Ul; Rehman, Fatima; Gul, Hemasa (Khyber Journal of Medical Sciences, 2024)
Background: The cause of female subfertility is influenced by multiple factors, and its diagnosis requires an invasive treatment including laparoscopy. Objective: To ascertain the prevalence of various factors contributing to female subfertility by the utilisation of laparoscopy. Material and methods: From July 31, 2021, to January 30, 2022, we carried out a cross-sectional research at the Department of Obstetrics and Gynecology, Hayatabad Medical Complex, Peshawar. 185 females with subfertility, ages 18 to 40, participated in the research. To choose the participants, we employed the non-probability consecutive sampling approach. To investigate the causes of subfertility, each female participant had laparoscopic surgery. Results: Our investigation included a cohort of 185 female participants, whose average age was 28.6±5.9 years. The mean duration of marriage was 8.12±1.3 years. The mean duration of subfertility was 4.74 ± 2.3 years. Primary subfertility was observed in 50.3% of females, while secondary subfertility was observed in 49.7% of females. Polycystic ovarian syndrome was the primary cause of subfertility, accounting for 21.1% of cases. This was followed by pelvic inflammatory disease (17.8%), tubal occlusion (14.6%), endometriotic deposits (13%), ovarian cysts (9.7%), peritubal and peri-ovarian adhesions (8.1%), and fibroids (6.5% of females). During laparoscopy, no identifiable cause may be detected in 9.2% of females. Conclusion; laparoscopy is an invaluable diagnostic technique for people experiencing subfertility.